Valuasi Ekonomi Terumbu Karang Pasca Penetapan Kawasan Konservasi Laut Sawu Di Kabupaten Kupang - Rahman, D. Umar; Risamasu, Fonny J. L.; Upa, H. M. D. Pua (Journal of Marine and Aquatic Sciences, 2020)
This research has been carried out in the Savu Sea Waters. The method used in data collection through interviews and questionnaires. Data collected and analyzed in this study are Direct Use, Indirect, Option, Existence and Bequest Value. The types of benefits identified and quantified are coral reef resources in the Savu Sea, especially those in Kupang Regency Coastal Area for Use Value, the Direct, Indirect, Option, Bequest, and Existence Value. Then a comparison is made between the direct value of coral reefs consisting of capture fisheries, aquaculture and tourism. While the value of indirect of coral reefs includes abrasion, carbon sink, fish nursery, spawning and Feeding Ground . And Non Use Value which consists of Option Value, Bequest, and Existence. The results of the analysis show that the value of direct is Rp. 218,027,971,623, 69 / year, indirect is Rp. 20,795,211,891.89 / year, option value is Rp. 3,967,284,324.32 / year, the existence is Rp. 4,121,520,000 / year, and the value of inheritance is Rp. 4,087,245,405.41. The highest Direct Use Value is in the form of capture fisheries value, while the lowest is in the form of aquaculture. Furthermore, for the economic value of Indirect as a Feeding Ground is the highest value compared to the others and the value of research benefits is the lowest. Meanwhile, the highest Non Use Value is the Existence and the lowest is the Bequest.